Optimalisasi Penilaian Kinerja Perawat Sebagai Upaya Peningkatan Pelayanan Komprehensif dan Keselamatan Pasien di Ruangan MPKP Kuantan Rumah Sakit Jiwa Tampan Provinsi Riau: Pengabdian - Erma Kasumayanti; Ulia Nelma; Ridha Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this activity is to optimize the performance assessment of nurses in the MPKP Kuantan Room, Tampan Mental Hospital, Riau Province, in order to improve the quality of comprehensive nursing services and patient safety. This optimization is expected to produce an objective, standardized, and sustainable performance evaluation system as a basis for improving nurse professionalism and the effectiveness of the implementation of the Professional Nursing Practice Model (MPKP). Community Service activities are carried out using the method of initial discussion, simulation and implementation of assessment as well as monitoring and evaluation. From the initial discussion through a mini workshop, it was agreed that issues related to performance assessment with activities carried out simulation and implementation of assessment as well as monitoring and evaluation. Simulation and implementation activities were carried out from July 22 to 30, 2025. Of the 14 nurses assessed, most had good performance. It is hoped that optimizing this assessment can increase the accountability of nurse performance, improve the quality of nursing care, and create a safe, effective, and sustainable service environment for patients with mental disorders.